Composite bioactive films based on smooth-hound viscera proteins and gelatin: Physicochemical characterization and antioxidant properties. (January 2018) - Abdelhedi, Ola; Nasri, Rim; Jridi, Mourad; Kchaou, Hela; Nasreddine, Benbettaïeb; Karbowiak, Thomas; Debeaufort, Frédéric; Nasri, Moncef
Abstract: The bioconversion of fish by-products through the development of biodegradable films offers the possibility to their valorization and, on the other side, to decrease the use of synthetic packaging, responsible for several ecological problems due to their non-biodegradability. Thus, in the present study, blend films (Bl-F) and bilayer films (Bi-F) based on commercial bovine gelatin (CBG) and smooth-hound viscera proteins, incorporated or not with sulfated polysaccharides (SP) or smooth-hound peptides (SHP) with molecular weight below 1 kDa, were successfully made using the casting method. Results of the scanning electron microscopy micrographs showed that the two biopolymers were compatible. Moreover, the mechanical properties analyses revealed that films based on the smooth-hound viscera proteins possessed higher tensile strength (TS) but lower elongation at break (EAB), compared to the gelatin film, where Bl-F were mechanically stronger and less deformable than Bi-F. Based on the differential scanning calorimetry analyses, Bl-F have the highest glass transition temperature (Tg ) (63–67 °C), confirming their glassy character at room conditions. In addition, Bl-F were found more effective on preventing moisture transfer, in a 30–84% relative humidity differential, than Bi-F, though the SHP addition slightly reduced the water vapor barrier efficiency. The analysis of surface properties demonstrated that all films possessed hydrophobic surface. Interestingly, SHP and SP addition greatly enhanced the antioxidant property of the films allowing them to be successfully used for food industries as bioactive packaging materials. Graphical abstract: Highlights: Composite films were made based on smooth-hound gel and gelatin. Surface property and water vapor permeability were affected by the type of additive. All films showed interesting mechanical and thermal properties. Peptides or polysaccharides addition improved the antioxidant properties of films.